Meta-Analysis of the Effect of STEM Approach on Students' Creative and Critical Thinking Skills in Physics Learning in Senior High School - Puti Zafirah Maharani Sastra; Yunita Jeliyah Jalis Putri; Fredy Pratama; Desnita Desnita (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2022)
This research aims to determine the effect of the STEM approach on the creative and critical thinking skills of high school students in learning physics. This research uses meta-analysis. The data in this research is secondary data from the results of research that have been investigated by other researchers. The data collection technique is using a literature study by looking for articles related to STEM learning. Sampling was carried out by purposive sampling technique. The sources of the research are 20 articles with national and international accreditation with criteria according to the problem formulation. This meta-analysis uses Cohen's d. effect size calculation method. The results obtained are first, based on the integrated learning model of the STEM approach that the STEM approach without the integrated model obtains the highest average effect value with an average effect of 2.93. Second, based on the learning material, the highest average value of the effect is on the dynamic electric material and Newton's law of gravity. Third, the application of the STEM approach to creative and critical thinking skills has an average effect of 2.66 for critical thinking skills, while creative thinking skills have an average effect of 1.47. Thus the STEM approach affects improving students' creative and critical thinking skills through integration with high school physics learning models and materials.